Sistem Pendukung Keputusan Pemilihan Kepala Desa Terbaik Menerapkan Metodethe Extended Promethee II (EXPROM II) - Nurlela Nurlela; Muhammad Syahrizal; Fadlina Fadlina; Abdul Karim (STMIK Budi Darma, 2020)
Decision Support System is a system that can help management in making the right decision, which is needed at a management level. Likewise at the Lubuk Pakam Sub-District Office in selecting the best village head. So far, the Camat Office has never determined the best village head in Lubuk Pakam Subdistrict, so that it encounters obstacles in choosing the village head election. SPK is able to provide alternative solutions to semi / unstructured problems for individuals or groups and in a variety of decision making processes and styles, SPK uses data, databases and analyzes of decision models. Seeing this, researchers are interested in conducting research by applying the Extended Promethee II (EXPROM II) method to elect the best village head in a decision support system. It is expected that the results of the research can help the Lubuk Pakam sub-district